From Causes to Remedial Attempts: The Phenomenon of Aversion to Learning and Using the Arabic Language - Alsaied, Mohamad Abdullah; Aldarmaki, Nouf Ali Musabeh bintamim; Alghefari, ‏Zoubida Talal (Journal of Posthumanism, 2025)
This study addresses the phenomenon of aversion to learning Arabic by investigating the multiple reasons behind the decline in enthusiasm for both learning and using the language—a decline that adversely affects the cultural and civilizational identity of the Arab nation. The research categorizes the causes into three main groups: the role of the school, the role of the family, and the role of society. In the educational sphere, the study reviews the inadequacies in Arabic language curricula and the imbalance between Arabic and foreign language classes. It also highlights the use of traditional teaching methods that rely on rote memorization rather than encouraging critical and analytical thinking. Furthermore, the study points out the insufficient preparation of teachers and their shifting focus toward scientific subjects and foreign languages, which results in a loss of confidence in Arabic that is subsequently transmitted to students. The research emphasizes that both emotional and practical engagement with the language are essential for cementing a strong linguistic identity. Regarding the role of the family, the study identifies it as the primary factor in instilling a love for Arabic in children. However, the increasing reliance on foreign caregivers, the lack of home libraries, and inadequate parental practices concerning reading and communication in Arabic have exacerbated the decline in the language’s appeal. In the societal domain, the study reveals the impact of technological dominance and media influence, which promote the extensive use of local dialects and foreign languages at the expense of Arabic. This shift undermines Arabic’s role in official, cultural, and artistic fields and affects its overall status. The research also discusses the effects of artistic productions and the political and economic conditions in Arab countries on shaping public perceptions of Arabic. Ultimately, the study proposes practical solutions such as reforming teaching methods and assessment practices, updating curricula to meet contemporary needs, and motivating teachers by equipping them with modern technological tools. It calls for strengthening national language policies and engaging government bodies, educational institutions, and civil society in supporting Arabic as a vital tool for preserving identity and culture. This study serves as an urgent call to reexamine educational and media systems to revitalize Arabic for building a cohesive civilizational future.